👤

Pouvez vous m'aider svp.
1) Développer,puis réduire l'expression
A = 5(7x - 2) + 3 (5 - 4x) - 8x

2) Factoriser l'expression
B = (5 - 3x) (2x + 3) + (5 - 3x) (3x - 1)


Répondre :

Bonsoir,
1) 
A =  5(7x - 2) + 3 (5 - 4x) - 8x
   = 5*7x + 5*(-2) + 3*5 + 3*(-4x) - 8x
   = 35x - 10 + 15 - 12x - 8x
   = 35x - 12x - 8x - 10 + 15
   = 23x -8x + 5
   = 15x + 5

2) 
B = (5 - 3x) (2x + 3) + (5 - 3x) (3x - 1)
   = (5-3x) [(2x+3) + (3x-1)]
   = (5-3x) [2x + 3 + 3x - 1]
   = (5-3x) [2x + 3x + 3 - 1]
   = (5-3x) (5x + 2)
 
Voilà, j'espère t'avoir aidé.